Modeling of Benzimidazole Derivatives as Antimalarial Agents using QSAR Analysis - Hadanu, Ruslin; Sitorus, Marham (UI Scholars Hub, 2024)
In this study, quantitative structure–activity relationship (QSAR) analysis was conducted on 20 homologous compounds of benzimidazole derivatives. The structures of the benzimidazole derivatives were optimized using the semiempirical Parameterized Model 3 method of HyperChem for Windows 8.0 to obtain 14 descriptors. Then, multiple linear regression (MLR) analysis was performed using the backward method. The results of the MLR analysis obtained four new QSAR equation models. Based on statistical criteria, model 1 was determined as the best QSAR equation model in predicting the theoretical IC50 values of the new benzimidazole derivatives. As many as 20 new compounds of benzimidazole derivatives were modeled, of which 13 new compounds (23, 24, 25, 26, 27, 28, 29, 30, 31, 37, 38, 39, and 40 compounds) were recommended for synthesis in the laboratory because these compounds of benzimidazole derivatives havethey theoretically had higher antimalarial activity than chloroquine